Agincourt - Hibbert, Christopher, 1924-2008. (Moreton-in-Marsh : Windrush Press, 1995)
Based firmly in contemporary chronicles, this account of the Agincourt campaign combines historical accuracy with a lucid and forceful narrative style.
Originally published: London : Batsford, 1978.
Includes bibliographical references (pages 136-138) and index.
Keywords: Agincourt, Battle of, Agincourt, France, 1415.; Military operations -- History; France